Lewis Thomas and droopy rabbit ears - Bashyam, Hema (The Rockefeller University Press, 2007)
In 1956, Lewis Thomas discovered that injecting rabbits with a plant protease called papain caused their ears to collapse. This experiment led to the identification of the endogenous proteases that cause the tissue destruction seen in diseases such as rheumatoid arthritis.